Challenges of Arabic Language Learning: Identity of Factors Affecting Students' Difficulties in Speaking - Priyanti, Karina Fatwa; Wahidul Akbar, Doni (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Arabic as an international language has a very significant role in the realm of education in Indonesia. However, many students face difficulties speaking Arabic. This study aims to explore the factors that influence Arabic-speaking difficulties and find effective solutions to overcome them. Using a qualitative method and a case study approach, the research involved 15 students from classes X-1 and X-2 of SMA Muhammadiyah 5 Jakarta as research subjects. We obtained data through interviews, observations, and documentation. We carried out data analysis through methods such as data reduction, data presentation, and verification. The results of this study indicate that students in grades X-1 and X-2 at SMA Muhammadiyah 5 Jakarta are still not maximized in pronouncing Arabic words and sentences due to several obstacles faced, such as educational background, lack of motivation, anxiety, and fear. Other factors include the environment, teaching materials, and the teaching process. The efforts that can be made by Arabic teachers are: giving extra attention and additional focus; providing a special approach; providing leniency; and creating interesting and effective teaching media. Based on the findings, it can be concluded that students' difficulties in speaking Arabic at SMA Muhammadiyah 5 Jakarta is a problem that needs to be addressed comprehensively. The implications of this study include encouraging students to learn more actively. Teachers use it as a guideline to enhance their learning strategies. It serves as the foundation for the school's efforts to enhance the Arabic language curriculum. This research could potentially assist students at SMA Muhammdiyah 5 Jakarta in overcoming their challenges in speaking Arabic.